Designing an Arduino Board-based Electronic Device Driven by GRBL Gru to Operate the Mini PCB Printing Machine - Nugroho Adi Wicaksono; Arief Goeritno (Universitas Syiah Kuala, 2022)
A compact integrated circuit is an intellectual property core at the heart of the decades of embedded devices on embedded systems. Using a microcontroller-based electronic module manufactured as desired or direct service of the board of Arduino as a control system for many purposes has become a certainty. Defining the problem formulations is related to the manufacture, assembly of the mechanical apparatus, and integrated wiring of several electronic modules. The acquisition of research contributions is expected to get the miniature embodiment of the physical machine equipped with a user program and perform the machine driver. The research methods consist of several steps to carry out each research objective. The miniature embodiment is carried out through (i) manufacturing and assembling to obtain the physical machine, (ii) integrating the electronic modules and all components and support systems by wiring to form an embedded system as a mini-PCB printing machine, and (iii) making a program structure based on Arduino IDE. Performing the machine driving mechanism is operating tests of calibration and moving on the axes of X, Y, and Z. Concluding based on the implementation process, testing, and analysis are carried out that the stages for performing the Mini PCB Printing Machine assisted by Arduino board with driven by GRBL Gru can be realized according to the initial design of hardware and software design.